Stigma among HIV/AIDS Patients in Africa: A critical Review - Yuh, Joyceline Ntoh; Ellwanger, Karen; Potts, Lydia; Ssenyonga, Joseph (Procedia - Social and Behavioral Sciences, 2013)
By the end of 2011 Africa had 23.5 million HIV infected people and 72% of the new HIV cases globally (UNAIDS, 2012). The mainly sexual transmission of HIV in the African context is associated with stigma especially among women (Rankin et al., 2005). HIV/AIDS stigma includes negative behaviors, denial, secrecy, fear and self-blame related to the disease (Deacon, Stephney & Proslendis, 2005). HIV/AIDS stigma is associated with sexual promiscuity, hinders disclosure of serostatus, and affects uptake of preventive programs (Zungu-Dirwayi, 2004). Though there is an acknowledgement of the negative effects of HIV/AIDS stigma, there is little research that has been conducted on this pertinent issue on the African continent with the largest number of HIV infected and affected people globally. Prevention of new HIV infections require the acknowledgement of the fact that stigma is attached to disclosure of status yet seropositive people still engage in risky behaviors (Prince et al., 2006). Therefore there is need to design strategies to counteract the negative effects associated to HIV/AIDS stigma at all levels.
Keywords: HIV/AIDS stigma; Sexual transmission; Disclosure; Risky behavior